2012
DOI: 10.1002/mpr.1364
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Strength and Difficulties Questionnaire from five European countries

Abstract: The Strength and Difficulties Questionnaire (SDQ) is a brief screening instrument for assessing emotional and behavioural problems in children and adolescents. This study examined the factor structure and validity of the self-report original English version of the SDQ and four of its many translations (German, Cypriot Greek, Swedish, and Italian). A total of 2418 adolescents from five European countries (Germany, Cyprus, England, Sweden, Italy), ages 12 to 17 years, participated. The sample was drawn from gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
105
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 39 publications
15
105
2
2
Order By: Relevance
“…This issue does not imply that SDQ cannot be used for in-country assessments. Recent studies have found similar results, indicating that the structure of the SDQ self-reported version in adolescents was non-invariant across cultures [38,39]. For instance, in the study of Essau et al [38] with five European countries, the factorial equivalence of the SDQ was rejected in the five and the three dimensional models tested.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…This issue does not imply that SDQ cannot be used for in-country assessments. Recent studies have found similar results, indicating that the structure of the SDQ self-reported version in adolescents was non-invariant across cultures [38,39]. For instance, in the study of Essau et al [38] with five European countries, the factorial equivalence of the SDQ was rejected in the five and the three dimensional models tested.…”
Section: Discussionmentioning
confidence: 85%
“…Nonetheless, the review of the literature shows that there are few studies of measurement invariance in the self-reported version of the SDQ [19,11,27,26,38,39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations